PENGARUH MOTIVASI, DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT PERTAMINA (PERSERO) MARKETING OPERATION REGION VII - Kasmin, Muh; Rahman, Muh. Rusydi (COMPETITIVENESS, 2018)
This study aims to analyze the influence of motivation on employee performance, work discipline on employee performance, organizational culture on employee performance and dominant variables affecting the performance of employees of PT Pertamina (Persero) Marketing Operatian Region VII. This research uses quantitative research. The population in this study was 359 employees of PT Pertamina (Persero) Marketing Operation Region VII. Samples in this study as many as 78 people with sampling techniques based on the formula slovin. The data were analyzed using multiple linear regression analysis.The results showed that the coefficient of motivational influence on employee performance was 0.014 with a tttabel < value (0.093 < 1.99) or a pvalue value = 0.926 > 0.05 which means that motivation has an insignificant positive influence on employee performance; coefficient of the influence of work discipline on employee performance of 0.344 with a tttabel > thitung value (2.704 > 1.99) or pvalue value = 0.009 < 0.05 which means that the discipline of work has a positive and significant influence on employee performance; coefficient of organizational culture influence on employee performance of 0.596 with a total value of > ttabel (4.028 > 1.99) or pvalue value = 0.000 < 0.05 which means that the organizational culture has a positive and significant influence on employee performance; and the most dominant variable affecting employee performance at PT Pertamina (Persero) is the organization culture with the highest beta value, which is 0.482. Keywords: Motivation, Work Discipline, Organizational Culture, Employee Performance